2009
DOI: 10.1523/jneurosci.2927-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Controls Growth Rate and Branching of Dopaminergic Axons

Abstract: Dopamine-releasing neurons of the substantia nigra pars compacta produce an extraordinarily dense and expansive plexus of innervation in the striatum converging with glutamatergic corticostriatal and thalamostriatal axon terminals at dendritic spines of medium spiny neurons. Here, we investigated whether glutamatergic signaling promotes arborization and growth of dopaminergic axons. In postnatal ventral midbrain cultures, dopaminergic axons rapidly responded to glutamate stimulation with accelerated growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 56 publications
(83 reference statements)
4
55
0
Order By: Relevance
“…A third possibility is that the altered response to amphetamine in the Vglut2 f/f;DAT-Cre mice is the result of a developmental defect of the mDA system caused by the targeted deletion of Vglut2. Indeed, in agreement with the recently suggested down-regulation of VGLUT2 in dopaminergic terminals in the adult rat nucleus accumbens (15), glutamate coreleased by DA neurons may play a developmental role, for example in synapse formation (38), and the loss of VGLUT2 in our conditional mutant mice may result in dysfunctional wiring of the DA terminals. Such dysfunction in turn could account for the blunted response to amphetamine in the adult mutant mice.…”
Section: Discussionsupporting
confidence: 92%
“…A third possibility is that the altered response to amphetamine in the Vglut2 f/f;DAT-Cre mice is the result of a developmental defect of the mDA system caused by the targeted deletion of Vglut2. Indeed, in agreement with the recently suggested down-regulation of VGLUT2 in dopaminergic terminals in the adult rat nucleus accumbens (15), glutamate coreleased by DA neurons may play a developmental role, for example in synapse formation (38), and the loss of VGLUT2 in our conditional mutant mice may result in dysfunctional wiring of the DA terminals. Such dysfunction in turn could account for the blunted response to amphetamine in the adult mutant mice.…”
Section: Discussionsupporting
confidence: 92%
“…Exposure to a glutamate gradient has been reported to induce the turning of growth cones of cultured rat cerebellar granule cells toward the glutamate source (5,65), and asymmetric distribution of filopodia in growth cones facing the glutamate source has been reported to form before the axons of Xenopus spinal neurons begin to turn (5). Bath application of glutamate has been reported to inhibit the movement of the axonal filopodia of cultured rat hippocampal neurons (8), although similar treatment has been reported to accelerate the growth and growth cone splitting of the axons of mouse ventral midbrain dopaminergic neurons (3). Brief exposure of mouse hippocampal neurons to kainate, an agonist of non-NMDA glutamate receptors, stalls the motility of their axonal growth cones (10).…”
Section: Camentioning
confidence: 99%
“…During development, glutamate also affects the growth, branching, chemotropic turning, and filopodial motility of migrating axons as well as synaptogenesis once axons have arrived at their target areas (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These glutamate-induced effects on axons have been attributed to the activation of various glutamate receptors on the plasma membrane of axons and to the subsequent increases in Ca 2ϩ concentration and resultant changes of the cytoskeleton in axons (2,(13)(14)(15).…”
mentioning
confidence: 99%
“…Similarly, it was shown that VGluT2 was expressed at low levels in vivo and that its expression decreased over development[6,13,14] so that it could be reliably detected only with RT-PCR based methods or indirect reporters[6,14]. These findings raised the possibility that the releasable glutamate content of adult dopaminergic neurons may be insufficient to support a functional glutamatergic phenotype and pointed to alternative developmental functions or an involvement in neuronal plasticity and repair [6,15,16,19]. …”
Section: Controversy About Functional Glutamatergic Signaling By Mesementioning
confidence: 99%
“…If a specialized subset of glutamatergic synapses of dopaminergic neurons indeed exist, these contacts may represent a specific stage of synaptogenesis or axon growth that is predominant early in development but remains observable in adult animals reflecting potentially continuing homeostatic or adaptive remodeling of the neuronal circuitry [6,15,16,19]. This hypothesis is at least consistent with the demonstration that dopaminergic axon growth is controlled by glutamate through ionotropic receptors [19] and may explain the gradual developmental downregulation of VGluT2 expression that approximately parallels the delayed postnatal development of the dopaminergic system [6,14,55,56].…”
Section: What Are the Operational Roles Of Glutamatergic Signaling Inmentioning
confidence: 99%